(N|LEKTRI^ESKIE SPOSOBY OBRABOTKI METALLOW (B/ s - (NbRASLAWSKIJ(B, (NwENIAMIN mARKOWI^s; (NzAHAROW(B, (NbORIS pETROWI^s ((NmOSKWAs (NsWERDLOWSK (B:s (NmA[GIZ(B,s, 1962)
(NzAKL(B. : (NS(B. 53-55s
(NwYP(B. 10 (1962, 56 (NS(B.)s
Keywords: (NoBRABOTKA METALLOWs